Impact of hypothalamic reactive oxygen species in the regulation of energy metabolism and food intake - Drougard, Anne; Fournel, Audren; Valet, Philippe; Knauf, Claude (Frontiers in Neuroscience, 2015)
Hypothalamus is a key area involved in the control of metabolism and food intake via the integrations of numerous signals (hormones, neurotransmitters, metabolites) from various origins. These factors modify hypothalamic neurons activity and generate adequate molecular and behavioral responses to control energy balance. In this complex integrative system, a new concept has been developed in recent years, that includes reactive oxygen species (ROS) as a critical player in energy balance. ROS are known to act in many signaling pathways in different peripheral organs, but also in hypothalamus where they regulate food intake and metabolism by acting on different types of neurons, including proopiomelanocortin (POMC) and agouti-related protein (AgRP)/neuropeptide Y (NPY) neurons. Hypothalamic ROS release is under the influence of different factors such as pancreatic and gut hormones, adipokines (leptin, apelin,...), neurotransmitters and nutrients (glucose, lipids,...). The sources of ROS production are multiple including NADPH oxidase, but also the mitochondria which is considered as the main ROS producer in the brain. ROS are considered as signaling molecules, but conversely impairment of this neuronal signaling ROS pathway contributes to alterations of autonomic nervous system and neuroendocrine function, leading to metabolic diseases such as obesity and type 2 diabetes. In this review we focus our attention on factors that are able to modulate hypothalamic ROS release in order to control food intake and energy metabolism, and whose deregulations could participate to the development of pathological conditions. This novel insight reveals an original mechanism in the hypothalamus that controls energy balance and identify hypothalamic ROS signaling as a potential therapeutic strategy to treat metabolic disorders.